Subject analysis of cancer research : Procedure and identification of core literature - Shieh, Jiann-Cherng; Yu, Chung-Yen; Shieh, Jiann-Cherng (Malaysian Journal of Library and Information Science, 2016)
Subject analysis is an approach for analyzing the development of academic research and paradigm shifts in Library and Information Science. Through content analysis and categorization of academic literatures, the focus in different development stages of research fields, such as research areas, issues of concern, and temporal and spatial shifts, is summarized and analyzed. This study proposes an analytical framework for the topics of electronic resources by adopting the Medical Subject Headings (MeSH) posted by the U.S. National Library of Medicine (NLM) as the basis for subject classification. The study covers cancer research as a subject case to verify and compare the databases of SCImago Journal and Country Rank and the bibliographies of PubMed biomedical literatures. Through systematic collection, collation, and analysis of raw data, variables such as specific key topics, number of publications, and year of publications are segmented for statistical analysis. The findings show that cancer research is a developing trend, and the compiled information provides a diversity of study topics for informatics and information behavior research.